PENGARUH MOTIVASI, PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA BENDAHARA SKPD KABUPATEN POLEWALI MANDAR - Fachruddin, Zarkiah (Indonesian Journal Of Economy Studies, 2022)
This study aims to test and prove empirically: (1) are the motivation influence on treasures ferformance; (2) are the education influence on treasures ferformance and (3) are the training influence on treasures ferformance. Theoretically, this research is expected to enrich and complement the knowledge in the field of human resource management so as to be useful to academics and practitioners. The type of research is explanatory research, population and sample in the study were 45 employees. The samples using total sampling technique, were analyzed by linear regression analysis with software SPSS 23. The results showed that: (1) Motivation negatively affect the performance of the treasurer, indicators of self-actualization needs security needs, the needs of self-esteem, physiological needs, and social needs, have not been able to influence the performance improvement treasurer: (2) Educational affect the performance of the treasurer, educational background to be a factor supporting the achievement of performance due to low educational treasurer cause treasurer difficult to absorb information related to financial management. Compliance is the educational background which is owned by the treasurer will be able to improve the performance of individuals, and can have an impact on improving the performance of the organization; (3) Training affect the performance of the treasurer, the treasurer training is needed to improve the skills and employability treasurer, training is done to facilitate the learning of the treasurer of the treasury regarding, for example, training of financial processing, reporting treasurer, salary and other mutations.